A Nation Dismembered. The 1920 Treaty of Trianon in Hungarian Poetry - Cristian, Réka M. (AMERICANA E-journal of American Studies in Hungary, 2020)
A Nation Dismembered. The 1920 Treaty of Trianon in Hungarian Poetry Selected and edited by Csilla Bertha and Gyula Kodolányi Hungarian Review: Budapest 2019 215 pages ISBN: 978-963-86217-3-3